Hukum Tindak Pidana Pembunuhan yang Dilakukan oleh Pengidap Skizofrenia Menurut Perspektif Hukum Islam : Law on the Crime of Murder Committed by People with Schizophrenia According to an Islamic Law Perspective - Patahuddin, Askar; Syaibani Mujiono; Mohamad Irgi Gobel (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This research aims to find out and understand criminal acts of murder committed by people with schizophrenia according to the perspective of Islamic law. This research uses a type of qualitative descriptive research (non-statistical), which focuses on the study of manuscripts and texts, using the library research method (literature review). The literature review contains theories that are relevant to the research problem. As well as using normative juridical and philosophical approaches. The research results found were as follows; First, based on the chronology of what happened, including, Chronology of Case Decision 135/ Pid.B/ 2016/ PN Stg, Chronology of Case Decision 94-K/ PM.II-09/ AD/ V/ 2016, Chronology of Case Decision 36/Pid. B/2019/PN Nla, Chronology of Case Decision 442/Pid.B/2018/PN Blb. The defendants were declared to have a personality disorder in the schizophrenia category as proven by experts brought in during the trial process. When committing murder, all of the defendants experienced symptoms such as mental disorders, delusional hallucinations, abnormal effects, and motor personality disorders, which are factors in schizophrenics who commit murder. Second, for the context or problems related to criminals suffering from schizophrenia, Islamic law agrees that this legal subject cannot be subject to sanctions or punishment even though the action is recognized as truly being a criminal act.